2019
DOI: 10.1186/s12889-019-7340-x
|View full text |Cite
|
Sign up to set email alerts
|

We still don’t know that our children need vitamin D daily: a study of parents’ understanding of vitamin D requirements in children aged 0-2 years

Abstract: Background Vitamin D deficiency has been highlighted as a serious public health problem in the United Kingdom. One in four toddlers are not achieving the recommended intake for their healthy development. This study uses quantitative and qualitative methods to explore parents’ perceptions, awareness and behaviours around vitamin D intake, and the acceptability of and factors affecting purchasing of food and drink fortified with Vitamin D in children aged 0–2 years old. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
1
30
0
1
Order By: Relevance
“…Receipt of supplements: Delivery actions for supply and distribution of food supplements require attention to effectively integrate food supplementation into infant and young child feeding practices [12] Targeting compliance: Supplements are created for specific target populations, and it is important for only those populations consume the supplements in adequate amounts [10]. Dosage compliance: Compliance with adequate dosage and frequency is required over long stretches of time, requiring effective filtration of information to beneficiaries [24].…”
Section: Process Evaluationmentioning
confidence: 99%
“…Receipt of supplements: Delivery actions for supply and distribution of food supplements require attention to effectively integrate food supplementation into infant and young child feeding practices [12] Targeting compliance: Supplements are created for specific target populations, and it is important for only those populations consume the supplements in adequate amounts [10]. Dosage compliance: Compliance with adequate dosage and frequency is required over long stretches of time, requiring effective filtration of information to beneficiaries [24].…”
Section: Process Evaluationmentioning
confidence: 99%
“…To the best of our knowledge, this was the rst study to describe and evaluate the effect of therapeutic intervention on prevention of hypovitaminosis D among children, and therapeutic intervention had a 2.21-, and 5.24-fold decreased risk of hypovitaminosis D compared with supplementation intervention and no supplementation, respectively. Besides, health professionals urge the parents to keep regular vitamin D supplementation [36] . Minkowitz et al reported that better adherence of guardians with low serum vitamin D levels to physicians' orders to remind their children of daily intake of vitamin supplements [37] .…”
Section: Discussionmentioning
confidence: 99%
“…however, compliance of children with follow-up blood collection varied. No vitamin D intervention due to guardians' lack of awareness that might be the main cause [36] , was like to expose their children to the increased risk of hypovitaminosis D and acute and chronic diseases including infectious diseases, autoimmune disorders and childhood dental caries [39] . Thus, although therapeutic intervention has shown a better effect in preventing hypovitaminosis D than voluntary supplementation, which prevention strategy to follow depends on certain factors, in particular the local health policy and compliance of guardians with blood collection.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this was the rst study to describe and evaluate the association of therapeutic intervention on prevention of hypovitaminosis D among children, and therapeutic intervention had a 2.21-, and 5.24-fold decreased risk of hypovitaminosis D compared with supplementation intervention and no supplementation, respectively. Besides, health professionals urge the parents to keep regular vitamin D supplementation [38] . Minkowitz et al reported that better adherence of guardians with low serum vitamin D levels to physicians' orders to remind their children of daily intake of vitamin supplements [39] .…”
Section: Discussionmentioning
confidence: 99%